Obstacles And Solution Toward English Learning During Covid-19 Pandemic - Pale, Erlinda Sonya (Universitas Nurul Jadid, 2021)
The process of online English learning during covid-19 pandemic brings both positive and negative impact. The positive impact could support learners to learn better. On the other side, the negative impacts could worsen the learning process. The present study was managed in order to answer three research questions mentioned as the problems faced by students and lecturers during English online learning in the pandemic of covid – 19, the most problem took place, and to find out possible solution to deal with the issue. The method implemented in this study was qualitative method with questionnaire and open-ended interview as the instruments. The result of the study pinpointed that atrocious internet was the problem occurred mostly during English online learning. The possible solution such as being focus in online learning, find places with good network, earlier material delivery and self-motivation were proposed by the students. Implementing blended learning was the solution recommended by the lecturers. To sum up, the obstacles in online English learning should be identified in order to be utilized as an input for the improvement of the learning process itself. Furthermore, the solutions could also become the factors to be considered as ways to enhance the process of English online learning.